2009
DOI: 10.1212/01.wnl.0000338533.88960.b9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trends in carpal tunnel syndrome

Abstract: Objective To assess temporal trends in carpal tunnel syndrome (CTS) incidence, surgical treatment and work-related lost time. Methods Incident CTS and first-time carpal tunnel release among Olmsted County, Minnesota, residents were identified using the medical records linkage system of the Rochester Epidemiology Project; 80% of a sample were confirmed by medical record review. Work-related CTS was identified from the Minnesota Department of Labor and Industry. Results Altogether, 10,069 Olmsted County resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
134
1
15

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(157 citation statements)
references
References 31 publications
7
134
1
15
Order By: Relevance
“…The repetitive use of the wrist and injuries to the wrist in contemporary populations were said to occur due to simple repetitive work and excessive use of computers in offices and at home rather than external occupational factors 7) . Thomsen et al 8) reported that excessive use of a mouse would cause carpal tunnel pressure (CTP), and Toosi et al 9) reported that use of a computer keyboard would be used for more than one hour, the median nerve would be compressed, and recommended taking appropriate rests when using a computer.…”
Section: Introductionmentioning
confidence: 99%
“…The repetitive use of the wrist and injuries to the wrist in contemporary populations were said to occur due to simple repetitive work and excessive use of computers in offices and at home rather than external occupational factors 7) . Thomsen et al 8) reported that excessive use of a mouse would cause carpal tunnel pressure (CTP), and Toosi et al 9) reported that use of a computer keyboard would be used for more than one hour, the median nerve would be compressed, and recommended taking appropriate rests when using a computer.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of CTS has been estimated at 3.8% in the general Finnish population and the disease is 2.5 times more common among women than men (2). The incidence of reported CTS in the general population of Olmstead County, Minnesota, from 2000-2005 was 4.4 per 10 000 and the average incidence of work-related CTS surgery was 1.1 per 10 000 (3). The prevalence of electrodiagnostically confirmed CTS from employee computer use and among active workers in healthcare and construction was 1.7% (4).…”
mentioning
confidence: 97%
“…20,21 The Rochester Epidemiology Project (REP) is an NIH-funded resource that comprehensively links the medical records of 95% of Olmsted County, MN, residents, irrespective of their health care provider. 22,23 It has been used extensively in many important population-based epidemiologic disease studies including several specific peripheral nerve diseases 10,[24][25][26][27][28] and has been shown to be representative of US populations. 22 In the present study, we estimated the prevalence of disease burden and mortality for all polyneuropathy cases in Olmsted County, MN.…”
mentioning
confidence: 99%